2014
DOI: 10.1080/1745039x.2014.919733
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofβ-conglycinin on growth performance, immunoglobulins and intestinal mucosal morphology in piglets

Abstract: One of the main causes of allergic reactions in young animals is β-conglycinin, an antigenic glycoprotein found in soya beans. Therefore, the objective of the study was to investigate the effects of a prior immunisation with β-conglycinin on growth performance, serum immunoglobulin levels and intestinal histology in piglets. Forty piglets (7 d of age) were randomly divided into four groups of ten piglets each. Piglets of Groups Im and Im+S were immunised twice by hypodermic injection with β-conglycinin at 500 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Allergenic proteins and anti-nutritional factors in soybeans are well known to depress growth, impair the integrity of the intestine, and induce allergies in young animals [19][20][21] . However, the mechanisms underlying the adverse effects of the allergens remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Allergenic proteins and anti-nutritional factors in soybeans are well known to depress growth, impair the integrity of the intestine, and induce allergies in young animals [19][20][21] . However, the mechanisms underlying the adverse effects of the allergens remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in agreement with the findings of Zhu et al [ 28 ], who noted a significant increase in serum concentrations of IgG and IgM in weaning piglets fed FSBM. Previous research showed that piglet immunity significantly decreased when β-conglycinin was not adequately deactivated during fermentation [ 35 , 36 ]. Our research revealed an increase in the immune function of broilers in the SC and TC groups that was directly related to the lower levels of glycinin and β-conglycinin in FSBM compared with SBM.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocyte proliferation is an important phase in the immune response of an animal and a proliferative response is antigen specific [ 44 ]. Piglet immunity is significantly reduced if β-conglycinin is not adequately inactivated during fermentation [ 45 , 46 ]. Our results indicated an improvement of immune function in piglets that directly correlated with reductions of glycinin (81.89%) and β-conglycinin (70.67%) in FSBM.…”
Section: Discussionmentioning
confidence: 99%
“…Standard histological procedures were performed as previously described [ 7 ] [ 28 ]. Briefly, longitudinal sections of duodenum, jejunum and ileum tissues (3 cm obtained from the proximal duodenum, middle jejunum and proximal ileum) were collected and flushed using physiological saline to remove the gut contents.…”
Section: Methodsmentioning
confidence: 99%